Hybrid Graphene Nanoribbons and MXene Anodes: Advancing Alternatives to Graphite for High-Performance Lithium-Ion Batteries - Salari, Meysam; Mohseni Taromsari, Sara; Hwang, Ling Wei; Naguib, Hani (Meeting abstracts (Electrochemical Society), 2025)
The increasing demand for lithium-ion batteries (LIBs) has highlighted the need for alternatives to synthetic and natural graphite, which currently dominate anode materials but are increasingly constrained by limited supply chains and intrinsic performance limitations. Natural graphite, predominantly sourced from specific geographic regions, is particularly vulnerable to geopolitical and economic pressures. Additionally, its theoretical maximum capacity of 372 mAh/g and its slow lithium-ion intercalation kinetics significantly hinder its utility for high-capacity, fast-charging applications. Despite advancements achieved through chemical and mechanical modifications of graphite, including doping and hybridization with other nanomaterials, its inherent limitations have driven research toward alternative carbon-based materials. Among these alternatives, graphene nanoribbons (GNRs) have garnered significant attention due to their distinctive quasi-one-dimensional (1D) and two-dimensional (2D) properties. These materials, synthesized via the chemical unzipping of multi-walled carbon nanotubes (MWCNTs), provide a high density of active edge sites for lithium-ion interaction, thereby overcoming some of the challenges associated with traditional graphene. However, the electrochemical performance of GNRs is heavily influenced by their crystalline structure and chemical composition, particularly the presence of oxygen functional groups. Excessive oxygen content, while beneficial for initial capacity, often results in high irreversible capacity losses and reduced cycling stability. In this study, the impact of controlled thermal reduction on the oxygen content and crystallographic properties of GNRs has been systematically investigated. It has been demonstrated that GNRs reduced at 500 o C achieve a reversible capacity of approximately 476 mAh/g at 0.05 A/g, although their performance declines at higher current densities. Conversely, GNRs reduced at 1000 o C exhibit lower capacities at low current densities but deliver superior high-rate performance, achieving 335 mAh/g at 0.5 A/g. This observed trade-off between capacity and conductivity highlights the necessity of strategies to balance these properties for optimal performance. To mitigate this trade-off, GNRs reduced at intermediate temperatures were hybridized with MXene (Ti 3 C 2 T x ), a highly conductive two-dimensional material known for its exceptional electrical properties and structural versatility. MXenes, a family of transition metal carbides and nitrides, are characterized by their metallic conductivity, hydrophilic surface, and low lithium-ion diffusion barriers (approximately 0.07 eV). These properties make MXenes particularly suitable for enhancing electron mobility and improving the electrochemical performance of hybrid anode materials. The hybridization process resulted in GNR/MXene composites that demonstrated significantly improved high-rate performance. At a current density of 1 A/g, capacities were enhanced by 47%, while at 5 A/g, an improvement of 36% was observed. The average capacity achieved at 0.5 A/g was approximately 320 mAh/g, indicating the effectiveness of this hybridization approach in delivering high capacities across a wide range of current densities. The results of this study highlight the potential of thermally modified GNRs and GNR/MXene hybrids as next-generation anode materials for LIBs. By addressing the limitations associated with traditional graphite, particularly its limited capacity and sluggish kinetics, these materials represent a promising pathway toward more efficient and scalable energy storage solutions. The enhanced performance achieved through the integration of MXenes can be attributed to their ability to facilitate rapid electron transport and their role in stabilizing the electrode structure during charge-discharge cycles. Further research is warranted to optimize the structural and chemical properties of these hybrid materials, with an emphasis on understanding the interaction mechanisms between GNRs and MXenes at the atomic level. Such efforts will be critical for realizing the commercial viability of these materials and for advancing the development of sustainable, high-performance energy storage systems.